A practical approach for beginning the process of technology roadmapping. (6th April 2009) - Lee, Jongsu; Lee, Chul-Yong; Kim, Tai-Yoo
The study addresses the need for a robust yet practical technology roadmapping method that considers four major factors: input from consumers who use the technology; input from engineers who develop the technology; the technological gap between the roadmapped technology and competing technologies; and future changes in consumer preferences. The proposed method begins by using conjoint analysis of survey-derived consumer data to assess consumer requirements. Expert opinion is elicited regarding the relative importance of engineering characteristics, and any technological gaps are assessed. Quality function deployment is used to interconnect the results. The roadmapping method is applied to power line communications.